THE IMPACT OF PUBLIC ADMINISTRATION POLICIES ON ECONOMIC DEVELOPMENT - Sidderatul Akbar; Agung Cucu Purnawirawan; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Public administration policies have a significant influence on a country's economic development. Through various regulations, programmes, and resource allocations, the government can shape the enabling or constraining environment for economic growth. Effective policies can encourage investment, increase productivity, and create jobs. Conversely, inappropriate policies can create bottlenecks and inefficiencies in the economy. The success of economic development largely depends on the government's ability to formulate and implement policies that are responsive to the needs of society and the dynamics of the global economy. Therefore, an in-depth understanding of the impact of state administrative policies on economic development is crucial for policy makers and other stakeholders in an effort to achieve sustainable economic growth and community welfare.